Benefit-cost analysis framework for evaluating inter-city transit investment - Guo, Jessica Y.; White, Kevin; Gong, Qi; Zheng, Jie (Midwest Regional University Transportation Center, 2008)
This report describes the development and application of a benefit/cost analysis (BCA) model to support the evaluation of investment decisions for intercity bus services. The model recognizes two principle types of intercity bus benefits: benefits that accrue to users of the transportation system and benefits that accrue to local areas from the presence of intercity bus services. The model was implemented into a MS Excel spreadsheet application, referred to as the IBBCA model. The IBBCA model takes as input various information relating to the proposed bus service, as well as the travel volume and LOS information corresponding to two scenarios: with the bus service and without the bus service. The model produces as output the total costs, total benefits, net benefits, and benefit-cost ratio associated with the intercity bus service being considered. Four out of the thirteen intercity bus routes proposed in Wisconsin's long range plan, Connections 2030, were analyzed using the IBBCA model. The analysis results indicate that most routes have relatively high benefit-cost ratios and are therefore worthwhile investments for Wisconsin. Madison-Wausau route gives the highest return of all in three future scenarios. The Madison-Green Bay route has the second highest return, followed by the Eau Claire-Green Bay and Wausau-Hurley routes. The results also show that user benefits are the dominating effects of intercity bus investments. Safety and environmental impacts, although they are smaller in magnitude, also provide significant societal benefits.
85 p.
Keywords: Benefit cost analysis; Bus transportation; Decision making; Economic impacts; Environmental impacts; Intercity travel; Investments; Level of service; User benefits; Safety; Wisconsin